A revision of the 2004 growth potential of towns in the Western Cape study - Van Niekerk, Adriaan; Donaldson, Ronnie; Du Plessis, Manie; Spocter, Manfred (Stellenbosch University, 2012)
CITATION: Van Niekerk, A., Donaldson, R., Du Plessis, M. & Spocter, M. 2010. A revision of the 2004 growth potential of towns in the Western Cape study. Stellenbosch University.